Multiport anterior retroperitoneal access for robotic-assisted partial nephrectomy: an innovative technique for renal tumour - Silvestri, Tommaso; Riolo, Sara; De Concilio, Bernardino; Zeccolini, Guglielmo; Costa, Giovanni; D'Aietti, Damiano; Knez, Roberto; Celia, Antonio (Frontiers in Surgery, 2025)
Robotic Partial Nephrectomy can be performed via transperitoneal or retroperitoneal access. The retroperitoneal approach offers direct access to the renal artery and reduces the risk of intestinal injury, especially in patients with prior abdominal surgeries or adhesions. This study presents a novel retroperitoneal robotic technique using anterior trocar placement with the patient in lateral decubitus. Access is gained through a pararectal incision, with the AirSeal trocar placed first, followed by the creation of an extraperitoneal working space and placement of robotic trocars. After docking, the renal hilum is isolated, the mass is enucleated following arterial clamping, and the collecting system is sutured selectively. The procedure ends with hemostasis and drainage tube placement. This is the first reported use of anterior retroperitoneal access with the patient in lateral decubitus, differing from previous techniques performed in the supine position. Advantages include avoiding intraperitoneal adhesions and improved assistant access. The technique is especially suitable for renal tumors in the middle or lower third of the kidney but can also be applied to upper pole lesions. Preliminary outcomes are promising; further research with larger cohorts is needed to validate its effectiveness.